Des approches prescriptives aux systèmes de gestion du risque fatigue - Philippe Cabon (Perspectives Interdisciplinaires sur le Travail et la Santé)
The impact of hours of work on employees’ health and safety is a critical issue given the increasing use of abnormal hours of work in a number of industries, services or transports. The prevention of fatigue associated with these hours of work is most often based on regulatory approaches that rule the duty time limitations and minimum rest time. These prescriptive approaches have several caveats, including for employees’ fatigue. This article presents an alternative for managing the risk of fatigue as close as possible to specific work constraints. The general principle of these fatigue risk management systems is presented and illustrated by a few examples. Their main limitations are also discussed.